(untitled) (World Science, 2023)
A solar dryer for drying fruits, vegetables, medicinal plants, and other agricultural products is proposed. This solar dryer (s/d) is simple to construct, and its drying chamber can be covered with polyethylene, polycarbonate, glass, metal sheet, or other material, depending on the dried raw material. As the results of the experiments in the solar dryer showed, the drying speed is high; products obtained in a solar dryer are of high quality - without preservatives and dyes, with a high content of vitamins, with good taste properties. For example, when drying cornel in a solar dryer, vitamin C losses are almost 2 times less than with natural drying. The shelf life of dried products is also increased when the storage conditions are properly observed. The high drying speed is explained by the enhanced convective movement of air in the dryer. The proposed solar dryer can be used on farms, as well as by urban residents, depending on the size of the dryer.